The Effect of Density and Different Tubifex sp Forms on The Growth and Survival Rate of Climbing Perch Larvae (Anabas testudineus Bloch) - Hilda Sawita Parhusip; Hamdan Alawi; Sukendi Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The research was conducted from 9 November until 30 December 2017 in Fish Breeding andHatchery Laboratory Faculty of Fisheries and Marine, University of Riau.  The aim of the research was to know the effect of density and Tubifex sp forms on the growth and survival rate of climbing perch larvae(Anabas testudineus Bloch).The method used in this research was the experimental method whereas the design used was a complete randomized design factorial with two factors namely first factor stocking density with two levels of each T2 (2 tail/liter), T4(4 tail/liter). While the second factor is the different Tubifex sp forms with three levels of fresh Tubifex sp (TS), frozen Tubifex sp (TB) and boiled chicken egg yolks enriched Tubifex sp (TK). To minimize the errors each treatment level was repeated 3 times. The best growth rate was obtained at the treatment T2TS (density 2 tail/liter with fresh form Tubifexfeed) with an absolute weight of 2,23 gr, absolute length of 3,98 cm, dayli growth rate of 12,68 %/day, and survival rate 100 %. The water quality condition were: water temperature 25,7-29 0C, pH 5,4-6,0and dissolved oxygen 5,1-6,0mg/l. Key word :Anabas testudineusBloch, density, Tubifex  sp form, and recirculation